Human fitting of pediatric and infant continuous-flow total artificial heart: visual and virtual assessment - Miyagi, Chihiro; Ahmad, Munir; Karimov, Jamshid H.; Polakowski, Anthony R.; Karamlou, Tara; Yaman, Malek; Fukamachi, Kiyotaka; Najm, Hani K. (Frontiers in Cardiovascular Medicine, 2023)
Background This study aimed to determine the fit of two small-sized (pediatric and infant) continuous-flow total artificial heart pumps (CFTAHs) in congenital heart surgery patients. Methods This study was approved by Cleveland Clinic Institutional Review Board. Pediatric cardiac surgery patients (n = 40) were evaluated for anatomical and virtual device fitting (3D-printed models of pediatric [P-CFTAH] and infant [I-CFTAH] models). The virtual sub-study consisted of analysis of preoperative thoracic radiographs and computed tomography (n = 3; 4.2, 5.3, and 10.2 kg) imaging data. Results P-CFTAH pump fit in 21 out of 40 patients (fit group, 52.5%) but did not fit in 19 patients (non-fit group, 47.5%). I-CFTAH pump fit all of the 33 patients evaluated. There were critical differences due to dimensional variation (p < 0.0001) for the P-CFTAH, such as body weight (BW), height (Ht), and body surface area (BSA). The cutoff values were: BW: 5.71 kg, Ht: 59.0 cm, BSA: 0.31 m2. These cutoff values were additionally confirmed to be optimal by CT imaging. Conclusions This study demonstrated the range of proper fit for the P-CFTAH and I-CFTAH in congenital heart disease patients. These data suggest the feasibility of both devices for fit in the small-patient population.